Benzo[1, 2-b:4, 5-b']dithiophene as a weak donor component for push-pull materials displaying thermally activated delayed fluorescence or room temperature phosphorescence. (February 2021) - Cardeynaels, Tom; Paredis, Simon; Danos, Andrew; Vanderzande, Dirk; Monkman, Andrew P.; Champagne, Benoît; Maes, Wouter
Abstract: In the search for high-performance donor-acceptor type organic compounds displaying thermally activated delayed fluorescence (TADF), triisopropylsilyl-protected benzo[1, 2- b :4, 5- b ']dithiophene (BDT-TIPS) is presented as a novel donor component in combination with two known acceptors: dimethyl-9 H -thioxanthenedioxide (TXO2) and dibenzo[ a, c ]phenazinedicarbonitrile (CNQxP). For a broader comparison, the same acceptors are also combined with the well-studied 9, 9-dimethyl-9, 10-dihydroacridine (DMAC) donor. Optimized BDT-TIPS-containing structures show calculated dihedral angles of around 50° and well-separated highest occupied and lowest unoccupied molecular orbitals, although varying singlet-triplet energy gaps are observed experimentally. By changing the acceptor moiety and the resulting ordering of excited states, room temperature phosphorescence (RTP) attributed to localized BDT-TIPS emission is observed for TXO2-BDT-TIPS, whereas CNQxP-BDT-TIPS affords a combination of TADF and triplet-triplet annihilation (TTA) delayed emission. In contrast, strong and pure TADF is well-known for TXO2-DMAC, whereas CNQxP-DMAC shows a mixture of TADF and TTA at very long timescales. Overall, BDT-TIPS represents an alternative low-strength donor component for push-pull type TADF emitters that is also able to induce RTP properties. Graphical abstract: Image 1 Highlights: A benzo[1, 2- b :4, 5- b ']dithiophene (BDT) donor is applied for TADF materials. The time-resolved photophysical properties are studied. Quantum-chemical analysis is used to estimate the charge-transfer character. Different triplet upconversion mechanisms are found (TADF vs TTA). Room temperature phosphorescence is turned on by the BDT donor unit.